Pola makan dan konsumsi alkohol sebagai faktor risiko hipertensi pada lansia - Nancy Swanida Henriette Malonda; Lucia Kris Dinarti; Retno Pangastuti (Jurnal Gizi Klinik Indonesia, 2012)
Background: Hypertension is one of the major chronic diseases in the elderly and the prevalence is constantly increasing. The results of Health Research Survey (Riskesdas) in 2007 showed that the prevalence of hypertension in the city of Tomohon was 41.6%. The prevalence of fatty foods consumption in Tomohon was relatively high, amounted to 17.2%. The proportion of alcohol consumer in North Sulawesi province was higher (17.4%) than the National proportion (4.6%), and Tomohon has signifi cantly higher alcohol consumers (36%). The consumption pattern of fatty foods and alcoholic beverages were factors that might increase the risk of hypertension.Objectives: To identify the infl uence of eating pattern and alcohol consumption as risk factors of hypertension in the elderly at Tomohon Municipality.Methods: This is an analytic observational study with case control design. Subjects were elderly people aged 60 – 65 years at Tomohon Municipality consisted of 76 cases (hypertensive) and 76 control (non-hypertensive). Data was collected through structured interviews, food frequency questionaire (FFQ ) was used to assess dietary pattern, mental health questionnaire (Self Reporting Questionnaire) was used to determine the condition of stress, waist-hip ratio measurement for obesity status, and blood pressure measurements. Data were analysed by bivariate and multiple logistic regression analysis.Results: The result of bivariate analysis showed that fat intake (OR=3.046; 95% CI:1.338 –6.933; p=0.008), alcohol consumption (OR=2.8; 95% CI:1.418 – 5.299; p=0.003), and obesity (OR=2.4; 95% CI:1.072 – 5.404; p=0.033) signifi cant increase the risk of hypertension. The intake of natrium, potassium and calcium, family history, smoking and stress showed no signifi cant association with hypertension. Statistical analysis revealed that the variables that become dominant risk factors for hypertension and affected the incidence of hypertension were fat (OR=3.303; 95% CI:1.346 – 8.10; p=0.009) and alcohol consumption (OR=2.792; 95% CI:1.347–5.789; p=0.006).Conclusion: High fat and alcohol consumption were risk factors that affect the incidence of hypertension amongst the elderly at Tomohon Municipality.